Communication and Education. Demand Analysis for Bachelor’s Degree Graduates in Organizational Social Communication - Gordillo, Alejandra María (2017)
Reflection “Communication-Education” is not limited to the analysis of practices, teaching-learning methodologies, the role of subjects in the dyad or the ideological issue that crosses the educational policies, but discuss the triad “teacher-knowledge-student” every time in a historical context. The binomial referred should also be enriched by scientific inquiry, which accounts for (among many other aspects) effective job placement of professionals (conceived as the fruit of this educational process of “Communication-Education”) in the immediate organizational environment of the higher education institutions. With this objective in view, an exploratory research was carried out (as a first and necessary step) to know more about the demand of social communicators in organizations (public, private or mixed) in the city of Chilecito, province of La Rioja (Argentina), an area which National University of Chilecito is inserted in period 2013-2014. Organizations are areas of professional intervention for Social Communicators with Institutional orientation: it is a wide and complex area of socio-cultural, administrative, economic, financial, political and ideological realities where they can deploy versatility of the competences and skills acquired during their degree training. On the other hand, investigating characteristics of the demand of these professionals constitutes a valuable resource at the moment of recognizing the feasibility and suitability of educational offer. These aspects have been the main motivations that have guided the development of the present paper.